Optimization Blended Learning Systems in Physics Learning Outcomes with Successful Skills in Management Learning - Motlan; Mihardi, Satria; Sinuraya, Jurubahasa (Advances in Social Sciences Research Journal, 2021)
The objective of this research is to develop blended-based management systems as well as its suitable learning device for physics subject of high school in Sumatera Utara Province. The research and development method with 4D design. Determination of the learning mode chosen as the basis for developing an optimized learning system with learning tools designed to meet online and face-to-face elements. Preparation for designing lesson plans, media, and student worksheets is inseparable from the adjustments that have been built in the blended learning system. Need Assessment is carried out by considering the implementation of learning, the number of subjects with different systems, and understanding variations in learning systems. The system built will be tested through user feedback. The conclusions that can be informed from the implementation of this development research are 1. Determination of the ’Flipped Classroom’ Blended Learning blended learning system. This lesson has been understood and needs adjustments to the meeting process compared to 50:50; 2. The use of web-based online classes makes it easier to change the face-to-face learning system; 3. Optimization is needed to increase the percentage of quality produced in the application of the selected blended system.